2011
DOI: 10.4314/ajpsy.v13i5.63106
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use predicts shorter duration of untreated psychosis and lower levels of negative symptoms in first-episode psychosis: a South African study

Abstract: Objective: Cannabis use/abuse is a common co-morbid problem in patients experiencing a first episode of psychotic illness (FEP). The relationship between the clinical presentation of FEP and cannabis abuse is complex and warrants further investigation, especially within the South African context. Method: We tested associations between recent/current cannabis use and duration of untreated psychosis (DUP), age of onset (AO), PANSS-rated (Positive and Negative Syndrome Scale) positive, negative and general psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Notably, a study performed by Burns and colleagues found that the prevalence of recent (past month) use of cannabis was 35% amongst participants with first-episode psychosis. 27 In the current study, past 3-month cannabis use (43%) cannot be directly compared to the past-month cannabis-use prevalence from the Burns et al . study, but both figures collectively indicate common frequency of recent cannabis use.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Notably, a study performed by Burns and colleagues found that the prevalence of recent (past month) use of cannabis was 35% amongst participants with first-episode psychosis. 27 In the current study, past 3-month cannabis use (43%) cannot be directly compared to the past-month cannabis-use prevalence from the Burns et al . study, but both figures collectively indicate common frequency of recent cannabis use.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, longer DUP was associated with cannabis use in the bivariate analysis (although the association lost significance in the regression), in contrast to a previous study amongst psychiatric patients at the same hospital in KZN conducted by Burns and colleagues, which showed that cannabis use was associated with shorter DUP. 27 An important difference between these two studies is that the Burns et al . study defined cannabis use in terms of recent (past month) use, whereas the current study assessed DUP against lifetime cannabis use.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Van Mastrigt et al (57) defined CU in terms of recent use and showed increased positive symptoms in cannabis users at psychosis onset; while Compton et al (60) reported a significant relationship between daily CU just before onset of psychotic symptoms, and an acute florid onset of psychosis. With respect to negative symptoms, Burns et al (58) defined CU in terms of recent use and reported significantly lower negative symptom scores at psychosis onset. Taken together, these findings suggest that increased positive symptoms and reduced negative symptoms at psychosis onset are likely to be associated with the acute effects of recent/current CU specifically.…”
Section: Clinical Presentation Of Psychosis In Cannabis Users – Are Tmentioning
confidence: 99%
“…Some authors have argued that lower negative symptoms in cannabis users is a function of selection, whereby individuals with negative symptoms cannot easily access cannabis due to the apathy, amotivation, and social withdrawal that comprises the negative syndrome (59). However this is unconvincing given the ease of access to cannabis in many countries such as the Netherlands and South Africa (58). …”
Section: Clinical Presentation Of Psychosis In Cannabis Users – Are Tmentioning
confidence: 99%
“…Findings regarding the relationship between cannabis use and negative symptoms are less clear. Some previous studies found that especially persistent users tended to report more negative symptoms in the long term (Gonzalez-Pinto et al 2011), while FEP studies found fewer negative symptoms in cannabis users compared with non-users (Burns et al 2010). Of note, these studies only reported differences on a trend level.…”
Section: Discussionmentioning
confidence: 96%